The Effects of Self Harming Behaviours of Youth in Child Welfare Care - Cheung, Connie; Goodman, Deborah (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2007)
This paper considers the clinical issue of self-harming behaviours, deﬁned as intentional self-injury that results in tissue damage. It is distinct from a suicide attempt, as self-harm does not occur within the context of a conscious wish to die. Self-harming behaviours among children and youth is a recent area of research. To date, studies indicate that in community samples, self-harming behaviours occur in as many as 35% of youth who are sampled (Gratz, 2001). Alarmingly, very little is known about self-harming behaviours among children and youth within the child protection system. This study, drawing from data gathered through a government-mandated reporting procedure of all children and youth in care,attempted to explore self-harming behaviours of children and youth in welfare care. While analyses did not focus explicitly on Aboriginal children and youth, it does consider differences in self-harming behaviours among minority and non-minority children and youth in care of the Children’s Aid Society of Toronto. Approximately half of all child welfare cases that go through the child protection system in Toronto fall under the responsibility of the Children’s Aid Society of Toronto. Although minority status was not signiﬁcantly related to the number of self-harming attempts or threats, results suggested that minority children and youth in care were less likely to use puncture-type behaviour (cutting, scratching, stabbing) as a means of serious self harm. Results suggest that although self- harm may be a universal phenomenon, culture may affect how children and youth in care engage in self-harming behaviours. Direction of future research should consider between-cultural effects and more importantly, how these culture-speciﬁc differences may impact on children and youth’s self-harming behaviours.